Investigation of biofilm formation and the associated genes in multidrug-resistant Salmonella pullorum in China (2018–2022) - Chen, Wenyan; Xu, Ziheng; Li, Changcheng; Wang, Can; Wang, Min; Liang, Jingzhen; Wei, Ping (Frontiers in Veterinary Science, 2023)
The study investigated biofilm (BF) formation, the BF-related genes and the antimicrobial resistance (AMR) profiles of Salmonella pullorum (SP) strains isolated from chicken farms in Guangxi, China during 2018-2022. A total of 627 SP strains were isolated from a collection of 4540 samples. Crystal violet staining was used to assess the BF-forming capacity of the isolates, and 36.8% (231/627) of the strains showed positive BF-formation capacity: among these strains, 24.7% (57/231) were strong BF producers, 23.4% (54/231) were moderate BF producers, and 51.9% (120/231) were weak BF producers. Polymerase chain reaction (PCR) testing of eight BF-related genes (csgA, csgB, csgD, ompR, bapA, pfs, luxS, and rpoS) in BF formation-positive strains revealed that more than 90% of them were positive for all the genes. Antimicrobial susceptibility test conducted on the isolates revealed that 100% (231/231) of the isolates exhibited resistance to at least one antibiotic, with 98.3% (227/231) demonstrating multidrug resistance (MDR). Minimum inhibitory concentration (MIC) and minimal biofilm eradication concentration (MBEC), determined using the broth microdilution method, showed increased AMR after BF formation of the bacteria. The optimal biofilm formation conditions (OBFC) were observed at 37 °C after 48 h of incubation, with an initial bacterial concentration of 1.2×10 6 CFU/mL. NaCl significantly reduced BF formation, while glucose and Trypticase Soy Broth (TSB) as carbon sources were positively correlated with BF formation. The results of the study emphasized the need for effective preventive and control strategies to combat the BF formation and MDR of SP in the field.